Life cycle carbon emissions inventory of brick masonry and light steel framing houses in Brasilia: proposal of design guidelines for low-carbon social housing - Lucas Rosse Caldas; Júlia Santiago de Matos Monteiro Lira; Pedro Corrêa de Melo; Rosa Maria Sposto (Ambiente Construído)
Abstract This study evaluated the CO2eq emissions during the life cycle of two social housing projects in the city of Brasilia. A house of ceramic brick masonry was compared to a light steel framing one. The life cycle carbon emissions assessment (LCCO2A) with a cradle-to-grave approach was used. The relation between the thermal performance of the wall systems and CO2eq emissions in the operational phase of the houses were evaluated using the DesignBuilder software. In addition, six scenarios composed of three CO2eq emission factors from the Brazilian electrical grid and two schedules of occupation of houses (full and part time) were evaluated. The brick masonry house presented less CO2eq emissions than the light steel framing one. For both houses, the operational phase was the most significant regarding the total CO2eq emissions (50% to 70%), followed by the construction (20% to 30%), maintenance (11% to 20%) and end-of-life (lower than 1%) phases. The results also showed the importance of considering different CO2eq emission factors for the Brazilian context in the operational phase. Finally, based on the results obtained, design guidelines for low carbon social housing were proposed.